2013
DOI: 10.1080/07315724.2013.767630
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Glucose Metabolism and Insulin Sensitivity with a Low-Carbohydrate Diet in Obese Patients with Type 2 Diabetes

Abstract: A low-carbohydrate diet was well tolerated and achieved weight loss over 24 weeks in subjects with diabetes. Glycemic control improved with a reduction in requirements for hypoglycemic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 36 publications
5
66
0
1
Order By: Relevance
“…Similarly, the evidence consistently showed significant improvements in HDL cholesterol with a low‐carbohydrate diet, with 10 studies finding a significant increase over control diet . It is also worth again noting that two studies showed a significant increase in LDL cholesterol in the low‐carbohydrate arm; the rest of the studies found no change or a decrease of LDL cholesterol. Adding a clause in future guidelines on monitoring LDL cholesterol or apolipoprotein B would further guide physicians in recommending this diet for their patients to ensure no additional CVD risk factor worsening, as individual results may vary.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Similarly, the evidence consistently showed significant improvements in HDL cholesterol with a low‐carbohydrate diet, with 10 studies finding a significant increase over control diet . It is also worth again noting that two studies showed a significant increase in LDL cholesterol in the low‐carbohydrate arm; the rest of the studies found no change or a decrease of LDL cholesterol. Adding a clause in future guidelines on monitoring LDL cholesterol or apolipoprotein B would further guide physicians in recommending this diet for their patients to ensure no additional CVD risk factor worsening, as individual results may vary.…”
Section: Resultsmentioning
confidence: 79%
“…In another study, the diet improved LDL cholesterol significantly in women but not in men . Two studies found that the diet resulted in significant worsening from baseline . However, the study by Hallberg et al reported no change between the test and control diets for measured apolipoprotein B, probably more pertinent to CVD risk than the calculated LDL cholesterol value, which is impacted proportionately by the significant rise in HDL cholesterol and decrease in triglycerides in the Friedewald equation used to calculate LDL cholesterol …”
Section: Resultsmentioning
confidence: 97%
“…35 In short-term studies, people with T2DM require less antidiabetic agents to control glucose levels and achieve improvements in glycated hemoglobin (HbA1c). 33,34,37 In some studies, these improvements are greater with a very low carbohydrate diet compared with other approaches, 41 but data are not consistent and there are no long-term studies convincingly demonstrating any greater benefit on HbA1c from VLCD's. Davis et al demonstrated similar modest weight loss but no significant improvement in glycemic control in those with T2DM on a low fat or low carbohydrate diet after 1 year.…”
Section: Glycemic Controlmentioning
confidence: 99%
“…33 The primary reduction in carbohydrate produces only a small reciprocal increase in protein and fat and therefore a reduction in total energy intake. 34,35 A systematic review demonstrated that low carbohydrate, Atkins-type diets were more effective at reducing weight than low fat, low energy diets over 6 months. Additionally, low carbohydrate, high protein diets were at least as effective as low fat diets up to 1 year.…”
mentioning
confidence: 99%
“…Several studies have shown that consuming a diet with a low glycemic index (GI) can reduce insulin resistance (König et al, 2014), blood lipid concentrations (Levitan et al, 2008), body weight (Krebs et al, 2013), and the levels of glycated hemoglobin (Wang et al, 2015a) and pro-inflammatory markers (Feliciano, das Graças, Alfenas, 2014) in blood. Other studies have shown low GI diets to be associated with increased satiety (Pardo-Beutimea et al, 2012) and the incidence of cancer (Truong, Yuet, Hall, 2014).…”
Section: Introductionmentioning
confidence: 99%